THE PROBLEMS SOLUTION OF ELASTICITY THEORY WITH SEPARATE DETERMINATION OF THE PURE STRAIN AND VOLUMETRIC DEFORMATION - Badalakha, I. K. (Science and Transport Progress, 2009)
In the article it is proposed to divide the overall deformation of elastic medium on two independent components – pure and voluminous ones, which are subjected to different physical relationships and determined separately. A comparative analysis of the results obtained is given.